Variétés de pidgin nigérian dans « Girls at War » et A Man of the People de Chinua Achebe, Jagua Nana de Cyprian Ekwensi et Sozaboy de Ken Saro-Wiva : questions de traduction de ces lieux de la variation - Catherine Paulin (Anglophonia)
This paper, by looking at some texts by Nigerian writers, deals with some problems that are raised by the translation of Pidgin Englishes in African literature in English-speaking countries. The reasons for the translation difficulties are linguistic and ideological. Translation choices, such as standardisation / « domestication », relocalisation / « foreignization », change of register… are determined by a set of parameters, such as time, cultural and literary norms as well as by the sociolinguistic reality and the potential it offers in terms of literary creativity.